Comparative Transcriptomic Analysis of Spermatozoa From High- and Low-Fertile Crossbred Bulls: Implications for Fertility Prediction - Prakash, Mani Arul; Kumaresan, Arumugam; Ebenezer Samuel King, John Peter; Nag, Pradeep; Sharma, Ankur; Sinha, Manish Kumar; Kamaraj, Elango; Datta, Tirtha Kumar (Frontiers in Cell and Developmental Biology, 2021)
Crossbred bulls produced by crossing Bos taurus and Bos indicus suffer with high incidence of infertility/sub-fertility problems, however, the etiology remains poorly understood. The uncertain predictability and the inability of semen evaluation techniques to maintain constant correlation with fertility, demands for alternate methods for bull fertility prediction. Therefore, in this study, the global differential gene expression between high- and low-fertile crossbred bull sperm was assessed using a high throughput RNA sequencing technique with the aim to identify transcripts associated with crossbred bull fertility. Crossbred bull sperm contained transcripts for 13,563 genes, in which 2093 were unique to high-fertile and 5454 were unique to low-fertile bulls. After normalization of data, a total of 776 transcripts were detected, in which 84 and 168 transcripts were unique to high-fertile and low-fertile bulls, respectively. A total of 176 transcripts were upregulated (fold change >1) and 209 were down regulated (<1) in low-fertile bulls. Gene ontology analysis identified that the sperm transcripts involved in the oxidative phosphorylation pathway and biological process such as multicellular organism development, spermatogenesis, in-utero embryonic development were downregulated in low-fertile crossbred bull sperm. Sperm transcripts upregulated and unique to low fertile bulls were majorly involved in translation (biological process) and ribosomal pathway. Using RT-qPCR, selected sperm transcripts (n=12) were validated in crossbred bulls (n=12) with different fertility ratings and found that the transcriptional abundance of ZNF706, CRISP2, TNP2 and TNP1 genes was significantly (p<0.05) lower in low-fertile bulls than high-fertile bulls and were positively (p<0.05) correlated with conception rate. It is inferred that impaired oxidative phosphorylation could be the predominant reason for low-fertility in crossbred bulls and transcriptional abundance of ZNF706, CRISP2, TNP2 and TNP1 genes could serve as potential biomarkers for fertility in crossbred bulls.